Los intereses tutelables y la dimensión de los perjuicios reparables en el Derecho francés de la responsabilidad civil extracontractual - Borghetti, Jean-Sebastién (Pontificia Universidad Católica del Perú, 2014)
In Tort Law, it is said that an individual mustrepair the damage he causes.  What is the extention of this maxim? Is this affirmation accurate? What is considered damage for Law?Jean-Sebastién Borghetti answers this and other questions as understood by French Law, seeking to delimit the French system of civil liability. In that sense, through this  article, the author proposes that not all affronts constitute a damage as understood by Law, and that not every damage can be repaired.

En la Responsabilidad Civil, se afirma que todoaquel que causa un perjuicio debe repararlo. ¿Cuál es el alcance de esta máxima? ¿Qué tan exacta es esta afirmación? ¿Qué es un perjuicio para el Derecho?Jean-Sebastién Borghetti responde estas y otras preguntas desde el Derecho francés, buscando delimitar el sistema francés de la responsabilidad civil. En ese sentido, a través del presente artículo, el autor propone que no todo agravio constituye un perjuicio para elDerecho, y que no todo perjuicio es reparable.
Legally protectable assets and the dimension of reparable damages in French Tort Law
Keywords: Law; French Law; Tort Law; Repairable Damages; Legally Protected Interest; Derecho francés; Responsabilidad civil extracontractual; Perjuicios reparables; Interés jurídicamente protegido; https://purl.org/pe-repo/ocde/ford#5.05.01